Retrospective evaluation of surgical outcomes using traditional, internal obturator muscle flap, and sacroischial sling technique for canine perineal hernia repair (Journal of Advanced Veterinary and Animal Research, 2026)
Objectives: This retrospective study compared the outcomes of three surgical methods: traditional technique, internal obturator muscle flap, and sacroischial sling (TT, IOMF, and SS) for the treatment of canine perineal hernias. Postoperative complications associated with each technique were also compared. Materials and Methods: 87 dogs (86 males, 1 female) with perineal hernia were included in this study. Dogs were grouped based on the surgical technique used: TT (30 sitesin 24 dogs), IOMF (30 sites in 26 dogs), and SS (53 sites in 37 dogs). Results: Surgical times were 36.8 ± 9.7 min for TT, 50.2 ± 13.6 min for IOMF, and 31.9 ± 11.53 min for SS. Both TT and SS were significantly faster than IOMF (p < 0.01). A comparative analysis of surgical outcomes revealed differing success and failure rates. The success rate of the IOMF group was higher (99.3%) compared to the TT group (80%); however, this difference was not statistically significant (p = 0.254). In contrast, the SS group demonstrated a statistically significantly greater success rate (98.1%) than the TT group (p = 0.008), indicating that it may be a more successful approach for perineal hernia correction in dogs. The TT group had the highest rate of temporary stranguria (20.8%) and required colopexy and cystopexy most frequently (16.7%). The SS group had the lowest rate of urinary incontinence (2.7%) and external anal sphincter muscle paresis(2.7%). However, this group exhibited the highest incidence of temporary dyschezia (8.1%) and a slightly elevated incidence of skin dehiscence. Wound complications were similar across all groups. The IOMF group had a higher incidence of external anal sphincter muscle paresis (26.9%) compared to both TT and SS. The complication rate of the SS group (7.0%, 13/185 events) was significantly lower than both TT (18.3%, 22/120; p < 0.01) and IOMF (18.5%, 24/130; p < 0.01) groups and required fewer additional procedures, indicating fewer overall complications. Conclusion: Overall, the SS technique is a practical, low-complication alternative for perineal hernia correction, offering results comparable to those of IOMF and superior to those of TT.J. Adv. Vet. Anim. Res., 12(4): 1421–1429, December 2025http://doi.org/10.5455/javar.2025.l1002